A rare case of intra-articular synovial sarcoma of the hip joint: a case report with intra-articular findings via hip arthroscopy. Issue 2 (27th February 2023) - Saito, Keiju; Kawabata, Yusuke; Kobayashi, Naomi; Iwashita, Hiromichi; Kato, Ikuma; Otani, Masako; Hayashida, Kenta; Fujita, Shintaro; Yoshida, Tomotaka; Choe, Hyonmin; Takeyama, Masanobu; Inaba, Yutaka
Abstract: Although synovial sarcoma is a relatively common soft tissue sarcoma, primary intra-articular cases are extremely rare. Herein, we report a case of primary intra-articular synovial sarcoma arising from the hip joint, that was initially treated with hip arthroscopy. A 42-year-old male presented with a history of pain in the left hip for 7 years. Radiography and magnetic resonance imaging revealed the primary intra-articular lesion and simple excision with an arthroscopy was performed. Histological findings revealed spindle cell proliferation with abundant psammoma bodies. SS18 gene rearrangement was confirmed by fluorescence in situ hybridization, and the tumor was diagnosed as synovial sarcoma. Adjuvant chemotherapy and radiotherapy were performed. Local control without metastasis was achieved 6 months after excision. This is the first case of intra-articular synovial sarcoma of the hip joint excised via hip arthroscopy. When an intra-articular lesion is identified, malignancies such as synovial sarcoma should be included in the differential diagnosis.